Faktor-Faktor Yang Mempengaruhi Pengungkapan Intellectual Capital yang Dimoderasi Profitabilitas - Fahmi Pratama Afiad; Eka Nurmala Sari; Syafrida Hani (Owner : Riset dan Jurnal Akuntansi, 2023)
This study was conducted with the aim of testing and analyzing the effect of firm size and managerial ownership on Intellectual Capital disclosure moderated by profitability in food and beverage companies listed on the Indonesia Stock Exchange directly or indirectly. The population in this study were all food and beverage companies listed on the Indonesia Stock Exchange, while the samples that met the criteria for sampling were observed for five years and as many as ten food and beverage companies were listed on the Indonesia Stock Exchange. This research approach uses associative research. Data collection techniques in this study using documentation techniques. and the analysis technique used is multiple linear regression analysis, hypothesis testing, coefficient of determination and Moderated Regression Analysis. The results show that partially firm size has no effect on Intellectual Capital disclosure, managerial ownership has a significant effect on Intellectual Capital disclosure, and indirectly return on equity is able to moderate the effect of firm size on disclosure. Intellectual Capital, return on equity is able to moderate the influence of managerial ownership on Intellectual Capital disclosure in food and beverage companies listed on the Indonesia Stock Exchange.